Acquiring, Analyzing, and Understanding Multimodal TikTok Short Video Data: The Case of Online Sex Worker Visibility Management - Helenius Teemu (Germany, 2025)
This paper introduces some key questions that affect how multimodal short video data on TikTok can be accessed, acquired, and analysed. The accompanying research ethical questions will also be highlighted. The issue of data collection is approached in ter ms of TikTok’s platform features that most readily affect how videos are made visible and available to users: audio centricity of content and its delivery via the For You Page (FYP) recommender algorithm. The specific context of data gathering, and multimodal discourse analysis are connected to the visibility management of sex workers on TikTok as affected by the platform’s content and visibility moderation. The paper presents work in progress approaches to data gathering for building multimodal corpora, mu ltimodal discourse analysis, and research ethics of TikTok videos , Additionally, some early findings of the analysis on online sex worker visibility management on TikTok are presented.
Proceedings of the 10th International Conference on CMC and Social Media Corpora for the Humanities